The Effect of 6 Months’ Treatment With Pasireotide LAR on Glucose Metabolism in Patients With Resistant Acromegaly in Real-World Clinical Settings - Witek, Przemysław; Bolanowski, Marek; Szamotulska, Katarzyna; Wojciechowska-Luźniak, Agnieszka; Jawiarczyk-Przybyłowska, Aleksandra; Kałużny, Marcin (Frontiers in Endocrinology, 2021)
Abstract Objective: The aim of the study was to evaluate glucose metabolism, as measured by glycated hemoglobin (HbA1c) levels and the need for antidiabetic medical treatment, in patients with acromegaly resistant to first-generation somatostatin receptors ligands (SRLs) treated with pasireotide long-acting release (LAR) in real-world clinical practice. Biochemical control of acromegaly, as measured by growth hormone (GH) and insulin-like growth factor 1 (IGF-1) levels, was also assessed. Study design: Two-center retrospective cohort of consecutive patients with acromegaly treated with first-generation SRLs at maximum doses, who had not achieved biochemical disease control. After SRLs were discontinued, patients were given pasireotide LAR 40 mg i.m. every 28 days. The dose was increased to 60 mg i.m. in patients for whom adequate control was not achieved after 3 months. Patients were given dietary and lifestyle advice, and antihyperglycemic treatment was modified as needed. Main outcome measures: Biochemical disease control parameters (GH and IGF 1 concentration), as well as HbA1c level at baseline and after 6 months. Results: In total, 39 patients with acromegaly were enrolled. GH concentration decreased (Δme = 1.56 µg/L, range 21.38–3.62, p <0.001) during 6 months of pasireotide LAR treatment. A worsening of metabolic status was observed, with an increase of median HbA1c (Δme =0.40%, range 0.20%–2.30%, p <0.001), and antihyperglycemic treatment intensification in 23 (59.0%) patients. The median decline in IGF 1 concentration was: 283.0 µg/L, range -682.7–171.6, p <0.001. IGF 1 reached the age-specific and gender-specific upper level of normal in 23 (59%) patients. Conclusions: Pasireotide LAR is an effective therapeutic option in patients with acromegaly refractory to first-generation SSAs. However, this therapy may result in pasireotide LAR-associated hyperglycemia, which requires early and aggressive antidiabetic medical therapy to prevent glucose homeostasis alterations.